Readiness assessment of public–private partnerships (PPPs) adoption in developing countries: the case of Tanzania. Issue 1 (12th June 2020) - Chileshe, Nicholas; Kavishe, Neema
Abstract : Purpose: The purpose of this paper is to examine the Tanzanian practitioner's readiness assessment for public–private partnership (PPP) adoption. This study is important as the readiness assessment enables the stakeholders to assess their capability and current status quo to implement new ideas such as PPPs. Design/methodology/approach: Underpinned by the theoretical lenses of innovation diffusion theory (IDT), this research undertakes semi-structured interviews with PPP practitioners within the Tanzanian affordable housing sector. The content analysis was used for the data as collected. Findings: "Lack of awareness and usage of PPPs framework models during the feasibility and subsequent implementation process", "Limited knowledge and skills required for PPP practitioners", "Poor capacity building", "Lack of engagement of experts during the viability and assessment process" and "Poor selection process of private partners giving rising to unsolicited proposals" are the main PPP features influencing the readiness process and fostering of innovation. Practical implications: The identification of the readiness approaches would support PPP policymakers and stakeholders with the government mechanisms for identifying the key areas needed to be addressed to improve the PPP implementation performance. Originality/value: Outputs of this study provide insights on how to foster a better understanding of the readiness assessment strategies and approaches for successfully implementing PPP in affordable housing projects.